The EFFECT OF AN INFUSION OF HIBISCUS SABDARIFFA L. IN HYPERTENSIVE PATIENTS FROM AN URBAN POPULATION: AN IMPORTANT COMORBIDITY BEFORE COVID-19.: Effect of an infusion of Hibiscus sabdariffa L. in hypertensive patients - MONTES, Rubio Perla Yuridia; FABELA, Illescas Héctor Enrique; ISLAS-, Munive Alvaro Guillermo; REYNOSO, -Vázquez Josefina; GARNICA, -Guerrero Beatriz; RUVALCABA-, Ledezma Jesús Carlos (African Journal of Traditional, Complementary and Alternative Medicines, 2024)
Background: Roselle (Hibiscus sabdariffa L.) has traditionally been used in folk medicine to treat hypertension; however, clinical studies are limited to show efficacy as an antihypertensive. Today, hypertension is an important comorbidity in the face of the covid-19 pandemic. The objective of this study was to assess the effect of a commercial H. sabdariffa infusion on blood pressure (BP) levels in hypertensive patients through a pilot clinical study. Materials and Methods: Patients with a previous diagnosis of hypertension were chosen, regardless of their BP figures, who frequently came for consultations at a health center. The infusion (10 g/240 mL) was administered orally daily for four weeks in 33 patients, 11 of them presented uncontrolled levels of BP. Results: Statistically significant differences were found in diastolic blood pressure (DBP) values, but not for systolic blood pressure (SBP) (n=33), suggesting that the values could decrease until being significant with a longer supplementation time or higher doses. In uncontrolled patients (n=11), both SBP and DBP showed a significant decrease. Conclusion: The results showed that the use of H. sabdariffa in this study could be useful in the management of patients with hypertension. However, future studies should be performed on larger samples so that effectiveness can be fully determined.